2007
DOI: 10.1364/ol.32.002125
|View full text |Cite
|
Sign up to set email alerts
|

Coherent exciton-plasmon interaction in the hybrid semiconductor quantum dot and metal nanoparticle complex

Abstract: We studied theoretically the exciton coherent dynamics in the hybrid complex composed of CdTe quantum dot (QDs) and rodlike Au nanoparticles (NPs) by the self-consistent approach. Through adjusting the aspect ratio of the rodlike Au NPs, the radiative rate of the exciton and the nonradiative energy transfer rate from the QD to the Au NP are tunable in the wide range 0.05-4 ns(-1) and 4.4 x 10(-4) to 2.6 ns(-1), respectively; consequently, the period of Rabi oscillations of exciton population is tunable in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 1 publication
3
83
0
Order By: Relevance
“…This rateequation approach describes non-coherent interactions at elevated temperatures. Very recently, several theoretical studies were performed for the quantum regime of exciton-plasmon interaction between a SQD/dye and MNP [16,17,18,19]. These studies revealed a novel feature of strongly-interacting hybrid nanocrystals -interference effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rateequation approach describes non-coherent interactions at elevated temperatures. Very recently, several theoretical studies were performed for the quantum regime of exciton-plasmon interaction between a SQD/dye and MNP [16,17,18,19]. These studies revealed a novel feature of strongly-interacting hybrid nanocrystals -interference effects.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures and small exciton broadening, the absorption line shapes are described by the Fano formula [20]. However, previous theoretical results [16,17,18,19] were based on the dipole approximation. The dipole approximation is valid when an exciton-MNP distance is large, compared to the sizes of components, and the excitonplasmon interaction is relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…We found that for the obtained solutions (10), one of the roots of the characteristic equation for the linearized system (6) on average values is always equal to zero, while other eigenvalues are satisfied to inequality Re (λ i ) < 0. Thus, the system moves to the boundary of aperiodic stability in the absence of external synchronization.…”
Section: The Formation Of Non-classical States Of Plasmons In Thementioning
confidence: 88%
“…The characteristic time of the dipoledipole interactions between NP and QD is in the order of 0.5 · 10 −4 ns, which is much less than the characteristic rate of exciton decay in the QD and is comparable to decay rate of plasmons. This situation corresponds to a strong coupling regime (see [10]). …”
Section: The Formation Of Non-classical States Of Plasmons In Thementioning
confidence: 99%
See 1 more Smart Citation